Hydrological response to changing climate conditions: Spatial streamflow variability in the boreal region. Issue 12 (10th December 2015) - Teutschbein, C.; Grabs, T.; Karlsen, R. H.; Laudon, H.; Bishop, K.
Abstract: In this paper we combined a multimodel ensemble based on 15 regional climate models with a multicatchment approach to explore the hydrologic sensitivity of 14 neighboring and rather similar catchments to changing climate conditions. Current (1982–2010) and future (2062–2090) streamflow was simulated with the HBV model. A diagnostic approach was used, which considered major behavioral catchment functions by using hydrologically relevant signatures related to overall water balance, flow duration curves and hydrograph attributes. Projected increases in temperature and precipitation resulted in increased total available streamflow, with lower spring and summer flows, but substantially higher winter streamflow. Furthermore, significant changes in flow durations with lower chances of both high and low flows can be expected in boreal Sweden in the future. This overall trend in projected streamflow pattern changes was comparable among the analyzed catchments but the magnitude of change differed considerably. This suggests that catchments belonging to the same region can show distinctly different degrees of hydrological responses to the same external climate change signal. We reason that differences in spatially distributed physical catchment properties within catchments are not only of great importance for current streamflow behavior, but also play a major role in the sensitivity of catchments to changing climate conditions. Key Points: Future streamflow responses are simulated for 14 similar, neighboring catchments in the boreal region Changes in streamflow patterns are comparable, but the magnitudes of change differ considerably Heterogeneous physical catchment descriptors control hydrologic catchment responses to climate change